Brazil – COVID-19 in Latin America and Caribbean : 2021 High Frequency Phone Surveys - Results Phase Two, Wave One - World Bank (Washington, DC, 2022)
Brazil has been one of the countries most affected by the COVID-19 pandemic in the region. In June 2021, it was the country with the second-highest rate of deaths per million and the fourth by the number of cases per million in Latin America and the Caribbean. The effects of the health crisis were broad and still evident a year and a half into the pandemic. In line with pre-existing vulnerability profiles, the pandemic affected the Brazilian population differently in the labor market. At the time of the survey, the proportion of people who lost their pre-pandemic job and were not working was 29.1 percent. This proportion was highest among the elderly (57.8 percent), those with primary education or less (42.7 percent), women (41.4 percent) and rural workers (38.7 percent). About 58 percent of those who lost their jobs became inactive, and most of the new inactive were women (68.9 percent). Simultaneously, 29.2 percent of the previously inactive entered the labor force during the pandemic, though one-quarter of them were unemployed in mid-2021. Women represented a majority among the new active (64.3 percent). Finally, the pandemic resulted in higher informality rates among those who remained employed.